Diagnostic Value of Stool Dna Testing for Multiple Markers Of Colorectal Cancer and Advanced Adenoma: A Meta-Analysis - Hua Yang; Bing-Qing Xia; Bo Jiang; Guozhen Wang; Yi-Peng Yang; Hao Chen; Bing-Sheng Li; An-Gao Xu; Yun-Bo Huang; Xin-Ying Wang (Canadian Journal of Gastroenterology)
BACKGROUND AND OBJECTIVES: The diagnostic value of stool DNA (sDNA) testing for colorectal neoplasms remains controversial. To compensate for the lack of large-scale unbiased population studies, a meta-analysis was performed to evaluate the diagnostic value of sDNA testing for multiple markers of colorectal cancer (CRC) and advanced adenoma.